Eğitimsel değişim ve öğretmen : biyoloji öğretmenlerinin yeni öğretim programı hakkındaki kişisel teorileri üzerine etnografik bir durum araştırması - Han, Çiğdem (My University, 2011)
Eğitim reformlarının temel amacı, eğitimin genel hedeflerine ulaşmasına yardımcı olmak amacıyla eğitim programlarının ve uygulamalarının iyileştirilmesidir. Değişim oldukça zor bir süreci ifade etmektedir. Çünkü eğitimde gerçekleşen değişim, hem yapısal hem de bireysel değişimi gerektirmektedir. Yapılan araştırmalarda eğitim reformlarına, öğretmenler tarafından direnç gösterildiği göze çarpmaktadır. Mevcut literatürde bu direncin kaynağı içsel ve dışsal faktörler olarak ayrılmakta, bu faktörlerin değişimin dinamiğini anlamaya yardımcı olduğu görülmektedir. Ancak bu karmaşık sürecin doğasının anlaşılması için farklı bakış açılarına ihtiyaç duyulmaktadır Bu çalışmada Thomas Kuhn’un bilimsel devrimlere bakış açısından yararlanılarak geniş ölçekli eğitim reformlarının doğası analiz edilmiştir. Geniş ölçekli eğitim reformlarının doğası bilimsel devrimlerin yapısı ile benzerlik göstermektedir. Çünkü geniş ölçekli eğitim reformları sisteme yeni bir kavramsal yaklaşım getirmektedir. Bu noktadan hareketle geniş ölçekli eğitim reformlarının nasıl yeni bir dünya ortaya koyduğunu göstermek için Türkiye’deki eski ve yeni biyoloji öğretim programları analiz edilmiş ve daha sonra katılımcı öğretmenlerin yeni öğretim programına karşı tutum ve yaklaşımları belirlenmeye çalışılmıştır. Bu çalışmada nitel araştırma yaklaşımı benimsenmiş ve etnografik durum araştırması metodolojik çatı olarak kullanılmıştır. Çalışmanın sonuçları eski ve yeni biyoloji öğretim arasında paradigma kayması olarak değerlendirilebilecek felsefi yaklaşım farklılıkları olduğunu göstermektedir. Ortaya çıkan bu farklılıklar, öğretmenler açısından değişme direncin genel nedeninin reformun kavramsal yapısını anlamadaki zorluklar olarak yorumlanmaktadır. Çünkü Türkiye’de halen çalışmakta olan çoğu öğretmen eski eğitim yaklaşımında yetişmiş ve deneyimlerini bu yaklaşım doğrultusunda gerçekleştirmektedirler. Bu bağlamda Türkiye’de gerçekleşen geniş ölçekli reformun uygulanma sürecinde bu sonuçlar dikkate alınmalıdır.

The main aim of any reform in education is to improve educational programs and practices which will, in turn, assist to meet overall objectives of education in more effective ways. Change is a difficult process, because, educational change of any significance involves changes in organizational structures, communications, resource allocation, practices, and beliefs and attitudes. Research acknowledges that reform efforts often face with a resistance, particularly on the part of teaching staff. Current literature on educational research usually attributes to external factors and internal factors as sources of the resistance to change on the teachers’ side. Although this categorization of the sources of resistance to educational change on teachers’ side is important and helpful in understanding the dynamics of educational change, multiple perspectives is needed to capture the nature and aspects of this complexity. In this study, we assumed that the nature of scientific revolutions as described by Thomas Kuhn provides one of the possible ways to analyze the nature of large-scale educational reforms and the complexity of the process. In one sense, large-scale educational reforms resemble scientific revolutions. As in paradigm shifts, large scale educational reforms bring new conceptual frameworks, introduce new educational aims and view on how people learn, require to adopt new teaching and assessment approaches and materials, etc. With this conceptual framework and in order to exemplify how a large scale educational reform introduces a new world for teachers, this study analyzed a curriculum reform recently taken place in secondary biology education in Turkey and examined beliefs and perceptions of teachers about educational reform. A qualitative oriented approach was employed and ethnographic case study was chosen as an appropriate methodological framework for this particular research. Detailed analysis presented that a dramatic paradigm shift has taken place at secondary level science education in Turkey. The curriculum reform experienced in Turkey has introduced a new world for teachers, which is fundamentally different from the previous one. In this new educational world, teachers face with new educational aims and objectives, new understanding of the nature of scientific knowledge, a different theory on how people learn and related teaching and assessment approaches. The results of this study can be interpreted that the overall reason for resistance to change on teachers’ side may the difficulty (if it is not impossibility) for teachers to comprehend the conceptual framework of the reform (or the new paradigm) as this requires denying the previous educational context in which they established themselves in. Considering the fact that the majority of the current biology teachers in Turkey completed their pre-service education in the framework of the previous curriculum and established themselves and their practices using the theories and approaches embedded in it, they, more than probably, will choose to refuse implementing the new education program with its new approaches.
Keywords: Eğitim; Öğrenim ve Öğretim_Biyoloji; Öğrenim ve Öğretim_Öğretmenler